Community Empowerment Strategy in Ecotourism Management: A Case Study in Baluran National Park - Hidayat, Agus Rohmat (Journal of Global Tourism, 2025)
This study aims to identify and analyze community empowerment strategies in ecotourism management in Baluran National Park, East Java. Ecotourism is considered a sector that can provide economic benefits while supporting environmental sustainability, but empowering local communities in its management still faces major challenges. This research used a qualitative approach with a case study design and data collection techniques in the form of in-depth interviews, questionnaires, and participatory observation. The results showed that although there were several efforts to empower the community, such as skills training and providing employment opportunities in ecotourism activities, the level of community participation in planning and decision-making was still limited. Factors that hinder empowerment include a lack of understanding of sustainable ecotourism, limited resources, and inadequate training. This research recommends the need for increased community involvement in planning, more inclusive management, and policies that better support the economic and social sustainability of local communities. The practical implications of this research are expected to provide a basis for more sustainable and inclusive ecotourism policies in Indonesia.